Orofacial Esthetic Scale and Psychosocial Impact of Dental Aesthetics Questionnaire: development and psychometric properties of the Finnish version - Campos, Lucas Arrais [UNESP]; Kämäräinen, Minna; Silvola, Anna-Sofia; Marôco, João; Peltomäki, Timo; Campos, Juliana Alvares Duarte Bonini [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2020)
Objective: To develop the Finnish version of the Orofacial Esthetic Scale (OES-Fi) and the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ-Fi) and estimate the psychometric properties of these instruments applied to adult Finns. Methods: The English versions of the instruments were translated into Finnish and back-translated. Thereafter, OES-Fi and PIDAQ-Fi were established in a pilot study. The factorial validity was estimated using Confirmatory Factor Analysis (CFI, TLI, SRMR) in independent samples (Test and Validation samples). The measurement invariance of the factorial models was tested using multigroup analysis (ΔCFI). Convergent validity [Average Variance Extracted (AVE)] and reliability [Composite Reliability (CR) and α] were estimated. Results: A total of 3636 individuals [mean age = 32.0 (SD = 11.6) years, 75% women] participated in the study. After refinements, the factorial model of the instruments showed an adequate fit to the data (CFI ≥0.94, TLI ≥0.90, SRMR ≤0.07) and showed measurement invariance in two independent samples (|ΔCFI| <0.01). Convergent validity (AVE = 0.54–0.82) and reliability (α = 0.86–0.94) were adequate. Conclusion: The data obtained using OES-Fi and PIDAQ-Fi were valid and reliable. Thus, these instruments could be useful for evaluating individual satisfaction with orofacial appearance and the psychosocial impact of dental aesthetics in a clinical or research setting.
Keywords: dental aesthetics; Psychometrics; validation studies